THE DIFFICULTIES IN PREPARING QUALIFIED ARABIC LANGUAGE TEACHERS IN NINGXIA, CHINA - Ma YaNa, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Arabic is the language of the Arabs and belongs to the flash language language-Semite language family. All used Arabic letters are mainly used in West Asia and North Africa and are now the official languages of 18 Arab countries and 4 international organizations. There are more than 400 million people in the world with Arabic as the official language, and Arab slang is more of a religious language in Islam. There are many Arabic dialects in different parts of the world and the differences are relatively large. Arabic is considered to be the most difficult language to learn in the world, just like Chinese. For beginners, it is hard to learn by self-study. Many Arabic teachers also have many difficulties in the process of teaching. This article allows us to sum up and summarize in detail, and find the solution afterward.